Features of the local environment of ions Mn2+ in ZnS crystals and nanocrystal ZnSxSe1-x:Mn and ZnxCd1-xS:Mn - Kovalenko, Oleksandr; Bulanyi, Mykhailo; Khmelenko, Oleg; Славний, Віталій (Physics and Chemistry of Solid State, 2025)
ZnSxSe1-x:Mn and ZnxCd1-xS:Mn nanocrystals were obtained by the method of self-propagating high-temperature synthesis. The EPR spectra of Mn2+ ions in these nanocrystals and in crystals of the same compounds grown from the melt under inert gas pressure were studied. It has been found that the ultrafine structure constant of the EPR spectra of Mn2+ ions in both nanocrystals and crystals has a jump-like dependence: in ZnSxSe1-x:Mn compounds at a parameter value of x = 0.2; in ZnxCd1-xS:Mn compounds at x = 0.6-0.7. These changes correlate with changes in other physical properties of nanocrystals, namely, the values of microstrain stresses and dislocation density.